Index of Social Vulnerability to Natural Disasters in Nepal - Kumar, Nand Kishor (BMC Journal of Scientific Research, 2024)
Social vulnerability to natural hazards is a significant issue in Nepal, a country prone to earthquakes, floods, landslides, and other disasters. Despite existing studies, there remains a gap in comprehensive vulnerability assessments that account for multiple hazards and socio-economic factors. This study aims to develop a modified Social Vulnerability Index (SVI) to assess social vulnerability across Nepal’s provinces using updated data and a multi-hazard approach. Using Principal Component Analysis (PCA), the study analyzed 18 socio-economic and demographic variables to derive three principal components explaining 88.55% of the variance in vulnerability. The SVI scores for each district were calculated and aggregated at the provincial level. Data from the 2021 Nepal Census and historical disaster records from 2015 to 2021 were used to quantify vulnerability. The study found significant regional differences in vulnerability. Madhesh (SVI = 21.84) and Karnali (SVI = 4.46) provinces were identified as very high vulnerability regions, while Gandaki province (SVI = -18.75) showed very low vulnerability. Terai regions were generally highly vulnerable, especially in terms of flooding. The findings emphasize the need for multi-hazard assessments in disaster risk management. The SVI is a practical tool for targeted disaster preparedness, resource allocation, and vulnerability monitoring over time. This study offers a comprehensive vulnerability assessment for Nepal, providing policymakers with essential tools to reduce disaster risks and enhance resilience across provinces.